Law Enforcement and the Role of Educational Institutions in Handling Cases of Sexual Harassment in Internships and the Workplace: Victim Perspectives and Policy Recommendations - Mutia Ananda Putri Sartika; Handoyo Prasetyo (Green Publisher Indonesia, 2024)
This research investigates the victim's viewpoint about the efficiency of the judicial system as well as the function of offices and educational institutions in addressing sexual harassment instances that occur in internship and employment settings. using the normative juridical approach of legal study to examine how normative legal rules are applied in each unique legal situation that arises in society. As a result, the literature review and different approaches to comprehending the nation's positive laws serve as the study's main foci. The present research further delineates many obstacles encountered by victims while attempting to get justice and proposes multiple measures for policy enhancement to enhance safeguarding and assistance for sexual harassment victims. In order to avoid and address harassment instances more skilfully, the recommended policy changes include bolstering reporting procedures, providing victim rights counselling, and enhancing training for office managers and educational personnel. It is anticipated that the findings of this research will aid in the creation of more accommodating and sensitive regulations addressing the problem of sexual harassment in internship and employment settings.